Strategi Pembelajaran Tari Bali pada Anak Usia Dini di Sanggar Taman Giri Agung Denpasar - I Gede Tilem Pastika; Ni Made Sukerni (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2022)
Balinese dance is famous for the complexity of movement that must be preserved. The people and the government fully support the spirit of preserving Balinese dance. Regeneration of Balinese dancers can start at an early age. If it is related to learning dance for early childhood with the Balinese dance rule, it is certainly the opposite. There is one studio that has succeeded in implementing Balinese dance learning and maintaining the quality of Balinese dance movements in early childhood. Taman Giri Agung Studio is an art studio established by the Bali Provincial Culture Service. This study aims to find out the strategies used by instructors in learning Balinese dance to participants belonging to early childhood and to find out the obstacles and efforts made in overcoming obstacles in the learning process. This research is descriptive qualitative research. Data collection is done by non-participant observation, literature study, interviews, and documentation. The results of this study indicate that the strategy used is to give freedom and not to force participants to follow instructions. The material provided for early childhood is an introduction to the basic movements of Balinese dance and Pendet Dance material. The learning method is a guided demonstration method conducted by 3 professional Balinese dance instructors. The evaluation stage is carried out once a year with a level increase system. The obstacles found in the learning process related to the participants' boredom were overcome by several efforts, including giving motivational words, giving rest breaks, and motivating by watching seniors' exercises.